The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.3766/jaaa.17.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Word Recognition in Young and Older Adults

Abstract: Dichotic word recognition was evaluated in free-recall, directed-attention right, and directed-attention left response conditions. All participants were right-handed and included a group of young adults with normal hearing and two groups of older adults with sensorineural hearing loss. Dichotic word recognition performance was best for young adults and decreased for each older group. A right-ear advantage (REA) was observed for all groups. REAs observed in the older groups were larger than those for the young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
45
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 30 publications
12
45
1
5
Order By: Relevance
“…The high performance in the directed attention stages in the dichotic listening tests, when compared with the binaural integration stage, has been reported previously (19) . The studies have shown that the difficulties observed in the stages of binaural integration, in dichotic listening tests, may occur because of the alterations in the skills of attention and/or working memory (20) .…”
Section: Resultsmentioning
confidence: 80%
“…The high performance in the directed attention stages in the dichotic listening tests, when compared with the binaural integration stage, has been reported previously (19) . The studies have shown that the difficulties observed in the stages of binaural integration, in dichotic listening tests, may occur because of the alterations in the skills of attention and/or working memory (20) .…”
Section: Resultsmentioning
confidence: 80%
“…To participate in the study, the subjects should meet the following eligibility criteria: age between 18 and 40 years; hearing thresholds within the normal range, i.e. a maximum of 25 dB at frequencies between 250 Hz and 8000 Hz, and at least complete secondary education, in order to avoid the variable "schooling" from interfering with the responses (13) . Individuals who did not accept to participate, did not meet the selection criteria or presented any factor that could interfere with the test, such as neurological changes and/or verbal fluency disorders, were excluded from the sample.…”
Section: Test Applicationmentioning
confidence: 99%
“…Brain imaging studies (Abe et al, 2002;Janowsky, Kaye & Carper, 1996;Johnson, Farnworth, Pinkston, Bigler & Blatter, 1994;Nusbaum, Tang, Buchsbaum, Wei & Atlas, 2001;Salat et al, 2005) suggest that age-related changes to the microstructure of the corpus callosum may occur, which may lead to a deficit in the interhemispheric transfer process. This degenerative change has the potential to alter the normal processing of auditory stimuli that are presented binaurally, and may help to explain left ear performance deficits observed in behavioural tests using dichotic measures, particularly for males (Gootjes, Van Strien & Bouma, 2004;Roup, Wiley & Wilson, 2006).…”
Section: Evidence For Structural Changes To the Cas With Agementioning
confidence: 97%